Feedback in the nonshifting context of the midwifery clinical education in Indonesia: A mixed methods study - Esti Nugraheny; Mora Claramita; Gandes R Rahayu; Amitya Kumara (Wolters Kluwer Medknow Publications, 2016)
Background: Clinical education in some countries applies a hospital-based learning approach where each student rotates to one division to another division (call of shifting). However, for clinical midwifery education in Indonesia each student remains in a community midwifery clinic (call of nonshifting). Because of the differences in the shifting system used, the question of "How is feedback in the nonshifting context of the clinical midwifery education being given?" needs to be explored. Materials and Methods: This was a mixed methods study and was carried out in a School of Midwifery in Indonesia during 2014 and 2015. We explored the supervisors' and students' perception on the feedback delivery. Students' perceptions were collected through focus group discussions whereas supervisors' perceptions were recorded through interviews. The quality of feedback was observed using a checklist. Qualitative data were analyzed using Atlas Ti and quantitative data were analyzed using a descriptive statistic method. Results: From the qualitative data, students and supervisors perceived their feedback as "more intensive." They reported authenticity in the monitoring and feedback from the day-to-day delivery of patient care with their supervisors. Students and supervisors also described their feedback as "more integrated." The feedback process stimulated students to value history taking, physical examination, and midwifery care. On the other hand, quantitative data from observations presented that "intensive and integrated feedback" were not supported by the quality of the feedback based on literature of the theory of facilitating learning (the mean was 4.67 on a scale of 0-9). Conclusions: The nonshifting clinical midwifery education can be a better alternative for facilitating the process of providing integrated and intensive feedback. To improve the quality of the feedback, training on providing feedback in a nonshifting context is fundamental in Indonesia.